The Role of Academic Historians in Growing National and State Awareness Reflections Record Tracks in Remembering Historical Events: Media, Methods of Field Trips in the Soekarno Porch and Historiography of Introduction to History - Yosef Dentis (Universitas Muhammadiyah Enrekang, 2022)
This research identifies the study of Intermediate Learning in History by helping students get to know historical knowledge directly and making history learning more real, clear, viral, interesting, and lively. It also helps sensitivity to the problems of the community environment outside the campus towards causal relationships that make history learning more permanent. This article was prepared using a qualitative descriptive research method. Data collected through direct and in-depth interviews and supported by archival documentation of photos and recordings. Research has found that the location of Serambi Soekarno is lacking and has not even been widely known and interested by the community, both the campus community and the wider community. The use and application of media and work-tour learning models in historical tours is a top program for students of the History Education Study Program in adding innovative and advanced means of enjoyment and interest in learning. Some of the studies that will be raised regarding: Profile of the Soekarno Porch, Function of Learning Media in the Soekarno Porch, The Role of Campus Communities and Academic Historians in Utilizing the Soekarno Site as a Collective Study of Introduction to History. Seeing the learning model with field trips gives innovative meaning in learning real history and rebuilding the history and oral traditions of local communities.